2013
DOI: 10.1007/s10900-013-9780-z
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Anthropometric Measures in a Multiethnic Population: Their Association with Prevalent Diabetes, Hypertension and Other Chronic Disease Comorbidities

Abstract: Body mass index (BMI) and waist circumference (WC) are two common anthropometric measures of obesity in clinical and public health practice. Consensus, however, remains elusive regarding their utility for predicting cardiovascular disease risk in multiethnic populations. We address this gap in the literature by analyzing cross-sectional data from the first round of the Los Angeles County Health and Nutrition Examination Survey, 2011. We characterized the relationships between BMI, WC, waist-to-hip ratios, wais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…However, the individual risk predictors we identified were generally consistent with those previously reported among inmates following admission. With the exception of kidney disease, females had higher prevalence of chronic conditions than males, which has also been reported previously (Binswanger et al, 2010; Booth, Prevost, & Gulliford, 2014; Freudenberg, Moseley, Labriola, Daniels, & Murrill, 2007; Tarleton et al, 2013). It is possible that females are more willing to report health conditions or agree to screening, or they may, in fact, be less healthy or more susceptible to certain chronic medical conditions when they enter the prison system (Lwebuga-Mukasa, Oyana, & Wydro, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…However, the individual risk predictors we identified were generally consistent with those previously reported among inmates following admission. With the exception of kidney disease, females had higher prevalence of chronic conditions than males, which has also been reported previously (Binswanger et al, 2010; Booth, Prevost, & Gulliford, 2014; Freudenberg, Moseley, Labriola, Daniels, & Murrill, 2007; Tarleton et al, 2013). It is possible that females are more willing to report health conditions or agree to screening, or they may, in fact, be less healthy or more susceptible to certain chronic medical conditions when they enter the prison system (Lwebuga-Mukasa, Oyana, & Wydro, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…A previous study has shown that the higher the BMI, the greater the risk of hypertension [21]. However, BMI does not accurately reflect the distribution of body fat [22].…”
Section: Discussionmentioning
confidence: 99%
“…19 To the extent feasible, measures from prior DPH data collection efforts (shown to be valid and reliable) were used (Office of Health Assessment and Epidemiology, LAC DPH, unpublished raw data, 2011). 26 Questions focusing on awareness and perceptions of the Choose Health LA Restaurants program (added in this round) were developed by the DPH.…”
Section: Methodsmentioning
confidence: 99%